Proceedings of the Americas Association of Sarcoidosis and Other Granulomatous Diseases (AASOG) 2017 annual meeting. - Bernstein, Richard C; Maier, Lisa A; Crouser, Elliott (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
On April 7th and 8th, 2017; the Americas Association for Sarcoidosis and Other Granulomatous Diseases (AASOG) held its annual scientific conference titled “Combining Transformative Sarcoidosis Research and Outreach to Improve Health Disparities” at the Penn State Health, Hershey Campus Conference Center.  Participants came from geographically diverse areas of the United States. The demographics of meeting speakers and attendees reflected the gender, racial and ethnic diversity of those who are engaged in the treatment of the disease.  The AASOG meeting was held in conjunction with an FSR-sponsored sarcoidosis patient-physician conference, providing a unique forum to enhance communication between patients, providers and researchers. Cutting edge topics at the meeting included immunology, microbiome, genomics, and challenges in diagnosis and treatment of vulnerable populations.  The meeting’s clinical foci were neurosarcoidosis, fatigue, and small fiber neuropathy.